Validation and reliability of a disease‐specific quality of life measure (the TranQol) in adults and children with thalassaemia major. (3rd November 2013) - Klaassen, Robert J.; Barrowman, Nicholas; Merelles‐Pulcini, Manuela; Vichinsky, Elliott P.; Sweeters, Nancy; Kirby‐Allen, Melanie; Neufeld, Ellis J.; Kwiatkowski, Janet L.; Wu, John; Vickars, Linda; Blanchette, Victor S.; Forgie, Melissa; et al.
Summary This study aimed to demonstrate the validity, reliability and responsiveness of a new disease‐specific quality of life (QoL) questionnaire for children and adults with thalassaemia major, the Transfusion‐dependent QoL questionnaire (TranQol). 106 participants (51 adults and 55 children) were recruited from six North American thalassaemia treatment centres with a mean age of 20·7 years (standard deviation [SD] 9, range 7–51 years). The mean total TranQol score was 71 (SD 17, 32–97) on a scale of 0–100. Patients with co‐morbidities had significantly lower scores (63 vs. 75, P = 0·001). TranQol scores showed substantial agreement (P < 0·001) with the Health Utilities Index Mark 3 (all patients, r = 0·65), the Pediatric QoL (children, r = 0·77) and the Short Form (36) physical (adults, r = 0·69) and mental summary scores (r = 0·76). In the subgroup who rated their QoL as better, there was a 4·0 point (SD 9·0) improvement in TranQol scores, from baseline of 67·1–71·1 one week later (P = 0·008). Test–retest reliability was excellent (intra‐class correlation coefficient, 0·93). The TranQol was valid, with acceptable correlation for all administered measures and was reliable and responsive to change. The TranQol can be incorporated into future studies of thalassaemia major.